Managing Invasive Mammals to Conserve Globally Threatened Seabirds in a Changing Climate. Issue 6 (24th May 2017) - Spatz, Dena R.; Holmes, Nick D.; Reguero, Borja G.; Butchart, Stuart H. M.; Tershy, Bernie R.; Croll, Donald A.
Abstract: Invasive mammals are an ongoing threat at many seabird breeding locations, while impacts from climate change can occur over broad time scales. Combining management strategies for invasive mammal and climate change impacts is important for mitigating current threats and maximizing seabird survival into the future. We assessed all 713 islands with threatened seabirds for conservation importance, immediate benefits of three invasive mammal management actions, and risk of climate‐change related flooding. Preventing invasions on the 397 islands without invasive mammals could benefit 72 seabird species. Invasive mammal eradication or localized action on 249 and 67 islands could benefit 71 and 46 seabird species, respectively. The long‐term risk of flooding on the 713 islands was low (69%). Low‐risk islands were concentrated where eradications or localized action were highlighted (75% and 100% of islands, respectively). These results inform management feasibility assessments and highlight rare opportunities to make significant contributions to seabird conservation.